Adaptation and Validation of a Chart‐Based Delirium Detection Tool for the ICU (CHART‐DEL‐ICU). Issue 4 (21st December 2020) - Krewulak, Karla D.; Hiploylee, Carmen; Ely, E. W.; Stelfox, Henry T.; Inouye, Sharon K.; Fiest, Kirsten M.
Abstract : OBJECTIVE: To adapt and validate a chart‐based delirium detection tool for use in critically ill adults. DESIGN: Validation study. SETTING: Medical‐surgical intensive care unit (ICU) in an academic hospital. MEASUREMENTS: A chart‐based delirium detection tool (CHART‐DEL) was adapted for use in critically ill adults (CHART‐DEL‐ICU) and compared with prospective delirium assessments (i.e., clinical assessments (reference standard) by a research nurse trained by a neuropsychiatrist and routine delirium screening tools Confusion Assessment Method (CAM‐ICU)) and (Intensive Care Delirium Screening Checklist (ICDSC)). The original CHART‐DEL tool was adapted to include physician‐reported ICDSC score (for probable delirium) and Richmond‐Agitation Sedation Scale score (for altered level of consciousness and agitation). Two trained chart abstractors blinded to all delirium assessments manually abstracted delirium‐related information from medical charts and electronic medical records and rated if delirium was present (four levels: uncertain, possible, probable, definite) or absent (no evidence). RESULTS: Charts were manually abstracted for delirium‐related information for 213 patients who were included in a prospective cohort study that included prospective delirium assessments. The CHART‐DEL‐ICU tool had excellent interrater reliability (kappa = 0.90). Compared to the reference standard, the sensitivity was 66.0% (95% CI = 59.3–72.3%) and specificity was 82.1% (95% CI = 78.0–85.7%), with a cut‐point that included definite, probable, possible, and uncertain delirium. The AUC of the CHART‐DEL‐ICU alone is 74.1% (95% CI = 70.4–77.8%) compared with the addition of the CAM‐ICU and ICDSC (CAM‐ICU/CHART‐DEL‐ICU: 80.9% (95% CI = 77.8–83.9%), P = .01; ICDSC/CHART‐DEL‐ICU: 79.2% (95% CI = 75.9–82.6%), P = .03). CONCLUSION: A chart‐based delirium detection tool has improved diagnostic accuracy when combined with routine delirium screening tools (CAM‐ICU and ICDSC), compared to a chart‐based method on its own. This presents a potential for retrospective detection of delirium from medical charts for research or to augment routine delirium screening methods to find missed cases of delirium.